1999
DOI: 10.1097/00004872-199917020-00012
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro validation, with histology, of intravascular ultrasound in renal arteries

Abstract: Intravascular ultrasound is a reliable technique for distinguishing renal arteries with or without a lesion. Both plaque development and local vessel narrowing may result in renal artery stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In human renal arteries, previous comparisons between the IVUS image and histopathological features have been reported (9,28); however, plaque components were not fully described. Our findings showed that necrotic core and dense calcium had significant correlations with positive remodeling in both RAS and CAD lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human renal arteries, previous comparisons between the IVUS image and histopathological features have been reported (9,28); however, plaque components were not fully described. Our findings showed that necrotic core and dense calcium had significant correlations with positive remodeling in both RAS and CAD lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Such adaptive enlargement of vessels can compensate for the accumulation of atherosclerotic plaque in vivo to preserve the vessel lumen (8). The remodeling process has not been elucidated in atherosclerotic RAS, and intravascular ultrasound imaging (IVUS) may be feasible and useful for the assessment of atherosclerotic RAS (911). …”
mentioning
confidence: 99%
“…The latter phenomenon was responsible for symptomatic RAS in 50% of patients, a prevalence of coarctation similar to that previously seen in our autopsy study. 3 Coarctation could be identified even after balloon dilatation in 44% of the patients. The present study is the first in which coarctation as a cause of RAS was evidenced clinically.…”
Section: Discussionmentioning
confidence: 93%
“…1,2 A recent intravascular ultrasound (IVUS) study in human renal arteries obtained at autopsy, however, suggested an alternative cause of RAS. 3 In that study, we observed that in 60% of the specimens, plaque accumulation, with or without compensatory vessel enlargement (ie, adaptive remodeling), caused lumen narrowing. This phenomenon was first described by Glagov et al 4 and, subsequently, by others.…”
mentioning
confidence: 89%
See 1 more Smart Citation